1997
DOI: 10.1002/(sici)1097-4644(19970801)66:2<245::aid-jcb11>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus (HPV) 16 E6 sensitizes cells to atractyloside-induced apoptosis: Role of p53, ICE-like proteases and the mitochondrial permeability transition

Abstract: Infection of cervical epithelial cells with certain high risk HPV genotypes is thought to play an etiologic role in the development of cervical cancer. In particular, HPV type 16 and 18 early protein 6 (E6) is thought to contribute to epithelial transformation by binding to the tumor suppressor protein p53, targeting it for rapid proteolysis, resulting in loss of its cell cycle arrest and apoptosis-inducing activities. Recent data indicate that factors responsible for triggering apoptosis reside in the cytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 58 publications
(74 reference statements)
1
16
0
Order By: Relevance
“…Apoptosis induced by other agents may be mediated by dierent pathways which may dier in their requirements for p53. Previous studies have shown that high level expression of HPV-16 E6 sensitizes cultured human ®broblasts, immortalized breast epithelial cells, or cervical carcinoma cell lines to apoptosis (Wahl et al, 1996;Xu et al, 1995;Brown et al, 1997). Our in vitro results show that E6 promotes a low level of apoptosis in normal human cervical keratinocytes, the natural target of HPV infection.…”
Section: Discussionsupporting
confidence: 64%
“…Apoptosis induced by other agents may be mediated by dierent pathways which may dier in their requirements for p53. Previous studies have shown that high level expression of HPV-16 E6 sensitizes cultured human ®broblasts, immortalized breast epithelial cells, or cervical carcinoma cell lines to apoptosis (Wahl et al, 1996;Xu et al, 1995;Brown et al, 1997). Our in vitro results show that E6 promotes a low level of apoptosis in normal human cervical keratinocytes, the natural target of HPV infection.…”
Section: Discussionsupporting
confidence: 64%
“…Such regulation of host DNA synthesis is exemplified by human adenoviruses (Li et al, 1997), Simian virus 40 (Conzen et al, 1997), human papillomaviruses (HPV) (Brown et al, 1997) and hepatitis B viruses (HBV) (Chirillo et al, 1997). Certain viral genomes encode proteins with highly conserved domains characteristic of Bcl-2-related proteins.…”
Section: Viral Proteins That Inhibit Apoptosismentioning
confidence: 99%
“…Other reports have also indicated that E6 can mediate its antiapoptotic activity in a p53-independent manner (Brown et al, 1997 ;Steller et al, 1996). HaCaT (Lehman et al, 1993) and C33A (Crook et al, 1991) cells have mutations in the p53 loci and the resistance to serum starvation-induced apoptosis is likely to be mediated by a p53-independent pathway.…”
mentioning
confidence: 91%